ANALISIS KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS V DI SD NEGERI 1 SUKAGALIH - Sarika, Riska; Gunawan, Dani; Mulyana, Herdi (IPI Press, 2021)
Reading comprehension skills are important for students' mastery, improvement, and knowledge. The purpose of this study 1) how the students' reading comprehension ability in grade V SD Negeri 1 Sukagalih 2) how the obstacles experienced by students in reading comprehension 3) how the efforts made by the teacher in improving reading comprehension skills. This study uses a descriptive qualitative method, where the subject is class V students. The research instrument uses tests and interviews. Based on the results of the study, it was concluded that 1) the results of the fifth grade students' reading comprehension test at SDN 1 Sukagalih obtained an average score of 67 which was included in the sufficient category. 2) from the results of the interview, the factors that become obstacles in the ability to read comprehension are motivation and interests, habits, student self-conditions, environmental influences, and reading materials. 3) From the results of interviews, the efforts made were to motivate students in reading, determine reading goals, teacher sensitivity to students who have difficulty in reading, use of methods and media in teaching, use of facilities and infrastructure.